Exploring the dynamic connectedness between commodities and African equities - Samuel Kwaku Agyei; Ahmed Bossman (Cogent Economics & Finance, 2023)
Market participants, regulators, and practitioners might have disregarded the prospective integration of African markets and the integration of commodity markets with traditional markets. We examine the nonhomogeneous return spillovers and contagion between 12 commodity sectors and African equities under the time-varying parameter vector autoregressions connectedness method. With daily datasets from February 2010 to February 2022, the average connectedness analysis suggests a low spillover transmission between commodities and respective African equity markets. We reveal that the return connectedness between commodities and African equities is largely driven by idiosyncratic spillovers. The results from the dynamic connectedness analysis reveal significant spillovers between the studied markets. Our findings underscore financial market contagion during stressed trading periods, suggesting that global commodity and African equity markets are not entirely immune to global market shocks. Therefore, prompt management of commodity price volatility and the integration between economies could result in controlled impacts of financial market contagion. Portfolio managers should deploy effective risk management strategies that capitalise on the nonhomogeneous roles of some assets as diversifiers, hedges, and safe havens across time horizons. Additional implications of our findings are discussed.
Keywords: 330; African equity markets; commodity classes; dynamic connectedness; financial market contagion; spillovers; TVP-VAR connectedness